Analysis of Marketing and Promotion Strategies in the Kecak Dance Performance at PT. Pengembangan Pariwisata Indonesia: A Case Study of Melasti Beach and Uluwatu - Mororizqi, Syahda Azafran; Albari, Albari (Program Studi Akuntansi IKOPIN, 2025)
This study aims to analyze the marketing and promotional strategies implemented by PT. Pengembangan Pariwisata Indonesia to increase tourist visits to the Kecak Dance performance, as well as to compare them with the marketing and promotional strategies applied at Melasti Beach and Uluwatu Temple. This research employs a qualitative approach through observation and interviews, utilizing the Marketing Mix and SWOT analysis methods to examine the strategies applied. The findings indicate that PT. Pengembanan Pariwisata Indonesia implements promotional strategies through collaborations with hotels, the use of promotional media such as billboards and flyers, the application of promotional innovations in the form of discounts and ticket bundling, and the utilization of digital technology through social media platforms such as Instagram and digital ticketing platform like Globaltix and Traveloka. In comparison, Melasti Beach relies on partnership-based promotions with third parties using a commission/fee system, while Uluwatu Temple emphasizes digital promotion through its official website and social media platforms such as Instagram and TikTok. For future research, it is recommended to examine tourist satisfaction with the marketing and promotional strategies implemented, in order to provide a more comprehensive perspective from the consumer side and to evaluate the effectiveness of the strategies carried out.